MENGEMBANGKAN EKONOMI KREATIF UMKM RADDINA CHOCOLATE MELALUI PENINGKATAN KUALITAS LAPORAN KEUANGAN - Nastiti, Ari Sita; Nuha, Gardina Aulin; Yulinartati (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Raddina Chocolate is a local MSME located in Klompangan Village, Ajung Sub-district, Jember Regency, which focuses on producing various processed chocolate products. Its product line includes decorative chocolate and bakery-based creations, distributed mainly through souvenir centers in Jember Regency. In managing its business, the partner encounters two primary challenges: financial records that do not comply with the SAK EMKM and limited marketing strategies. This community engagement program aims to strengthen Raddina Chocolate’s role in the creative economy by enhancing the quality of its financial reporting and developing more innovative marketing approaches. The activities were implemented at the partner’s business site through a combination of lectures and hands-on practice. The PKM team delivered training on financial bookkeeping in accordance with SAK EMKM as well as the use of digital media for marketing purposes. Evaluation was conducted through discussions and interviews to assess participants’ comprehension and the overall effectiveness of the program. It is expected that this initiative will foster business growth, open new employment opportunities, and inspire the surrounding community to engage in the creative economy sector, ultimately contributing to regional economic development.